Empowering Churchill: Exploring Energy Security in Northern Manitoba - Kvern, Michael; Fitzpatrick, Patricia; Fishback, LeeAnn (The Arctic Institute of North America, 2022)
To those living in Churchill, Manitoba, having power means much more than being able to turn on the lights. Using Churchill as a case study, we examine how local context can improve the suitability of energy security definitions for communities in northern Canada. Churchill is an isolated northern municipality with no road access but is connected to the electrical grid. Energy consumption data were collected from utility providers and organized into a community energy profile. Semi-structured interviews (n = 23) and a community workshop (n = 12) identified challenges, opportunities, and a vision for Churchill’s energy system. High per capita energy consumption, especially of transportation (jet fuel) and heat (electricity and propane) sources dominate Churchill’s energy profile. The reliance on air travel and need for heating are realities that define energy systems in the North. Participants expressed desire for increased use of renewables and improved energy efficiency. Churchill is reliant on external sources of power and there is a need for agency and local decision making. Jurisdictional realities and the community’s desire for consideration of local context mean energy security definitions should take a regional approach. Recognizing these findings, we propose a new definition of energy security that fits the circumstances and desires of Churchill and the North. Pour les gens de Churchill, au Manitoba, avoir de l’énergie ne signifie pas seulement être capable d’allumer les lumières. En nous appuyant sur une étude de cas au sujet de Churchill, nous examinons en quoi le contexte local peut permettre d’améliorer le caractère approprié des définitions de la sécurité énergétique pour les communautés du Nord canadien. Churchill est une municipalité nordique isolée sans accès routier, mais elle est reliée au réseau électrique. Des données sur la consommation d’énergie ont été recueillies auprès de fournisseurs de ce service public et organisées en un profil énergétique communautaire. Des entrevues ...